Efficacy of Peristeen® transanal irrigation system for neurogenic bowel in the pediatric population. Issue 6 (December 2019) - Gordon, Tiffany; Vandersteen, David R.; Dryjanski, Laura; Carpenter, Jennifer
Summary: This study demonstrates significantly improved bowel symptoms and satisfaction with Peristeen® use in pediatric patients with neurogenic bowel. The longer patients used Peristeen®, the greater the reduction in severity of their Neurogenic bowel and the greater the satisfaction with their bowel management. Image 1